Pectin reduces environmental pollutant-induced obesity in mice through regulating gut microbiota: A case study of p, p′-DDE. (September 2019) - Zhan, Jing; Liang, Yiran; Liu, Donghui; Ma, Xiaoran; Li, Peize; Zhai, Wangjing; Zhou, Zhiqiang; Wang, Peng
Abstract: Background: The prevalence of obesity has raised global concerns. Environmental pollutants are one of the main causes of obesity. Many studies have demonstrated that dietary fiber could reduce obesity induced by high-fat diets, but whether environmental pollutant-induced obesity can be reversed is still unknown. Objectives: This study aimed to investigate the effects of pectin on obesity induced by a typical environmental pollutant p, p'-dichlorodiphenyldichloroethylene (p, p′-DDE) and explore the underlying mechanism by which pectin reversed p, p′-DDE-induced obesity. Methods: p, p′-DDE was used to induce obesity in C57BL/6J mice and pectin was supplied during and after cessation of p, p'-DDE exposure. Body and fat weight gain, plasma lipid profile and insulin resistance of mice were assessed. Gut microbiota composition and the levels of short-chain fatty acids (SCFAs) as well as the receptor proteins and hormones in the SCFAs-related signaling pathway were analyzed. Moreover, p, p′-DDE levels in various tissues of mice were detected. Results: Pectin supplementation reversed body and fat weight gain, dyslipidemia, hyperglycemia and insulin resistance in p, p′-DDE-exposed mice. Furthermore, pectin apparently altered the p, p′-DDE-induced microbial composition and then promoted the levels of SCFAs in colonic feces as well as the expression of G-protein coupled receptors and the concentration of hormone peptide YY (PYY) and glucagon like peptide-1 (GLP-1). Pectin treatment also significantly reduced p, p′-DDE accumulation in mice tissues during p, p′-DDE exposure but did not change p, p′-DDE metabolism after termination of p, p′-DDE exposure. Conclusions: Pectin had a good effect on reducing p, p′-DDE-induced obesity through regulating gut microbiota and provided a potential strategy for the treatment of environmental pollutant-caused health problems. Graphical abstract: Unlabelled Image Highlights: p, p′-DDE-induced obesity in mice could be reversed by pectin supplement. Pectin restored p, p′-DDE-induced obesity by regulating gut microbiota and SCFAs levels. Reducing p, p′-DDE accumulation by pectin may contribute to decreasing the impacts.